Finnish University Students’ Retrospective Reflections on Transitioning from Upper Secondary Education: Traits of Career Learning - Kicki Häggblom; Jessica Aspfors; Pia Nyman-Kurkiala (Nordic Journal of Transitions, Careers and Guidance)
With support from guidance counselors and teachers, young people are expected to not only acquire the knowledge and skills to handle their future choices of studies and employment but to also take an active role in developing their careers and designing their lives. Finland has been acknowledged as having one of the most professionalized school-based career education systems, with a long tradition of guidance counseling taught in class as a school subject in addition to support provided individually or in groups. A qualified guidance counselor is responsible in both cases. The formal foundation for career education is in place, which sets expectations regarding students’ career learning. This article aims at exploring career learning in Finnish general upper secondary education (GUS) through university students’ reflections on their experiences of transitioning from GUS to higher education. A pedagogical perspective is applied using the principles of educative teaching as the theoretical approach. The data consist of written career stories produced during the 2022–23 academic year by university students (N = 19) enrolled in specialization studies required to acquire these qualifications as guidance counselors in Finland. The data are interpreted using reflexive thematic analysis. The metaphor of career as a journey is used to generate three themes: (a) the tour guidance paradox, (b) destination is subject to change, and (c) souvenirs are rare. The findings show the informants recognize career development as a lifelong process. To support an individual’s career learning process, discussion of a strong pedagogical approach to career education is needed.   Abstrakt Med hjälp och stöd av vägledare och lärare förväntas unga inte bara skaffa sig kunskaper och färdigheter för att hantera sina framtida studie- och yrkesval, utan också aktivt forma sina karriärer och sina liv. Finland är känt för sitt professionaliserade skolbaserade system för karriärvägledning, med en lång tradition av ett schemalagt skolämne som undervisas i klassrummet samt individuell och gruppbaserad elev- och studiehandledning. En behörig studiehandledare ansvarar för båda formerna. Dessa formella grunder för karriärvägledning skapar i sin tur förväntningar på elevernas karriärlärande. Den här artikeln syftar till att utforska karriärlärande genom universitetsstuderandes retrospektiva reflektioner över sina erfarenheter av övergången från gymnasieutbildning till högre utbildning. Ett pedagogiskt perspektiv tillämpas med principer för bildande undervisning (educative teaching) som teoretisk ansats. Datamaterialet består av karriärberättelser skrivna av universitetsstuderande (N = 19) under läsåret 2022–2023. Studerandena var inskrivna på specialiseringsstudier för att bli behöriga elev- och studiehandledare i Finland. Datamaterialet har analyserats genom reflexiv tematisk analys. Metaforen “karriär som en resa” användes för att skapa tre teman: (a) resan är en vägledningsparadox, (b) destinationen kan förändras och (c) souvenirer är sällsynta. Resultaten visar att informanterna ser karriärutveckling som en livslång process. För att stödja en individs karriärlärandeprocess behövs en diskussion om ett starkt pedagogiskt grepp i karriärvägledning.   Nyckelord: karriärlärande; karriärvägledning; bildande undervisning